Plant Diversity in an Intensively Cultivated Vineyard Agroecosystem (Langhe, North-West Italy) - Mania, E.; Isocrono, D.; Pedullà, M.L.; Guidoni, S. (South African Journal of Enology and Viticulture, 2016)
In areas of intensive agriculture, wild plant species are confined to field margins, thus they play a role in protecting biodiversity. The aim of the present study was to assess plant diversity in an area of intensive viticulture and to evaluate, for the first time, the impact of field margins on vineyard flora biodiversity. The study was conducted in North-West Italy, were five categories of floristic lists in vineyard-margin pairs were sampled and compared. Five margins were identified: grass-covered (A) and bare (B) headlands, small (C) and wide (D) woodlands, and shrub and herbaceous (E) areas. Two hundred and fifty-two taxa were found, although only 19 were widespread. Differences among categories emerged, highlighting the high floristic complexity of the sites surrounded by wide wooded areas (D). The findings suggest an influence of margin size, in addition to margin type, on the floristic richness of the vineyard. Moreover, an inverse relationship between species richness and both the presence of Poaceae and the degree of soil grass coverage emerged. Enhancing biodiversity, at landscape and field level, by the appropriate management of cover crops and ecological infrastructures, within and around vineyards, could be a strategy in sustainable viticulture. The increase in plant species richness is not an end in itself, but it might help to promote biodiversity at different trophic levels.